Peningkatkan Literasi Siswa melalui Program Kerja Revitalisasi Perpustakaan dalam Kegiatan Kampus Mengajar 7 di SDN Kertosari 03 - Rintan Amalia Rohar; Astri Widyaruli Anggraeni (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to enhance student literacy through a library revitalization program conducted during the Kampus Mengajar 7 activities at SDN Kertosari 03. The program includes three main activities: categorizing books by genre, creating reading corners, and forming reading groups. The research employed a descriptive qualitative method, with data collected through observations, interviews, and documentation during the mentoring process. The results show that library revitalization significantly improved students' reading interest and literacy skills. Categorizing books made it easier for students to access reading materials that matched their interests, while reading corners provided a conducive environment for reading activities. The formation of reading groups was also effective in developing literacy skills through a collaborative approach. In addition to improving literacy, this program also succeeded in creating social changes, such as the emergence of new institutions in the form of reading groups and increased active student participation in literacy activities. Based on these findings, it is recommended that other schools in resource-limited areas adopt a similar approach to comprehensively enhance student literacy.